(untitled) (Studia Prawnicze / The Legal Studies, 1981)
In a capitalist state self-government takes mainly the form of decentralized administration which is exercised by organs other than those of state or govern- mental administration. In a socialist state self-government assumes various forms in all the domains of social life. In People’s Poland the principle of self-govern- ment is of constitutional importance. Its two features are essencial: 1) right of a certain community to appoint its own representatives, and 2) certain degree of independence in solving its problems in a direct way or by the representation. Comparison of structural position of self-government in a capitalist and in a socialist state is made here in relation to two spheres: 1. As to the relation between self-government and state, the Author states that: 1. In a capitalist state administration exercised by state apparatus is a structural rule. In principle, self-government is allowed only as an exception of this rule. A capitalist state can function without self-government all-together. On the contrary, a socialist state cannot function without self-government. The principle of self-government results objectively from the political system based on government by the people and from economic system based on social owner- ship of the means of production. 2. Self-administration as a concept is opposed to state only when it concerns capitalist state. On the other hand, in a socialist state — as antagonistic class contradictions disappear — development of self-government strengthens the state. New, formerly unknown forms of self-government appear. Contemporary capitalist state attempts to apply such forms as well. 3. In a capitalist state self-government constitutes only a particular form of decentralized administration. In a socialist state self-government means participation in the management of state affairs in all stages of managerial process, thus becomes not only an institution of administrative but first of all — that constitutional law. II. As to the relation between self-government and society, the Author states: 1. In a capitalist state self-government is identified with its administrative organs. Certain communities are mainly treated as social substratum of the above mentioned organs; In a socialist state certain social communities may constitute subjects of self-government combining both direct democracy and democracy based on representation. 2. In a socialist state self-government of a given social community needs no power to enforce obedience of the members of this community. That is the reason why self-government appears not only in the form of a compulsory union but also in the form of social organization. In relation to these organizations basic tasks of which lie in the external sphere, one has to differenciate between selfgovernment in their internal matters and the role which such organizations play among other social communities. 3. Thus, in a socialist state self-government is of consequently social character. Essencial features of the organs of self-government are not only their social composition and the character of their activity, but also the fact that they act in the name and interest of social groups which had set them up. Self-government can also fulfill the tasks appointed by the law, i.e. tasks of state administration. However, distinction should always be made between state organs of non-professional (social) personal composition and social organs of self-administration. General development of various forms of self-government is a regularity of a socialist state also because in farther future such state will be transformed into communist social self-government.